1989
DOI: 10.1523/jneurosci.09-09-03326.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that L-dopa-induced rotational behavior is dependent on both striatal and nigral mechanisms

Abstract: Parkinson's disease results from the death of the dopamine-containing neurons in the substantia nigra pars compacta (SNC). This is accompanied by a loss of dopamine in brain regions, such as the corpus striatum, which receives input from dopaminergic neurons in the substantia nigra (SN). Since the corpus striatum is the primary target for these dopaminergic neurons, it has long been thought that the corpus striatum is the principal region affected. It was, therefore, natural to assume that replenishing dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(98 citation statements)
references
References 22 publications
(26 reference statements)
8
90
0
Order By: Relevance
“…In support of this hypothesis, L-DOPA-induced rotations can be blocked by intranigral infusion of SCH23390 (37). However; intrastriatal microinjection of SCH23390 delayed the C͞L-DOPA transition from locomotor activity to stereotypy and reduced the induction of c-fos mRNA.…”
Section: Discussionmentioning
confidence: 76%
“…In support of this hypothesis, L-DOPA-induced rotations can be blocked by intranigral infusion of SCH23390 (37). However; intrastriatal microinjection of SCH23390 delayed the C͞L-DOPA transition from locomotor activity to stereotypy and reduced the induction of c-fos mRNA.…”
Section: Discussionmentioning
confidence: 76%
“…In unilaterally MPTP-lesioned rhesus monkeys, a single intraventricular injection of GDNF produced improvement in motor function, which was correlated with DOPAC and HVA levels in the lesioned nigra but not in the striatum (Gerhardt et al, 1999). In unilaterally 6-OH-dopamine-lesioned rats, l-DOPA-induced rotational behavior was temporally correlated to the duration of increased DA levels in the substantia nigra rather than the striatum (Robertson and Robertson, 1989). In rats, neuroleptic-induced increases in hind limb muscle tone, a measure of rigidity, requires blockade of nigral DA D 2 /D 3 receptors (Double and Crocker, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…These include the ability of olanzapine (Stockton and Rasmussen, 1996), like clozapine (Chiodo and Bunney, 1983), but unlike haloperidol (Chiodo and Bunney, 1983), to produce a selective depolarization of DA neurons in the VTA, but not in the substantia nigra, and the role of dopaminergic neurotransmission in the substantia nigra in motor behaviors (Gerhardt et al, 1999(Gerhardt et al, , 2002Robertson and Robertson, 1989). Studies in animals have demonstrated that a number of motor behaviors require normal nigral as well as normal striatal dopaminergic function.…”
Section: Discussionmentioning
confidence: 99%
“…Being the output nuclei of the basal ganglia, the EP and the SNr mediate motor stimulant effects of antiparkinsonian drug treatment (Marti et al, 2004;Robertson and Robertson, 1989). In these two structures, there is a high density of D1 receptors on the terminals of 'direct pathway' (striatonigral) axon fibers (Dawson et al, 1988;Savasta et al, 1986a, b), promoting the release of both GABA and dynorphin (reviewed in Cenci and Lindgren, 2007).…”
Section: Discussionmentioning
confidence: 99%